PENDAMPINGAN KELOMPOK IBU DALAM MEMBERIKAN STIMULASI TUMBUH KEMBANG BAYI DENGAN MEMBERIKAN RANGSANGAN TAKTIL (PIJAT BAYI) DI WILAYAH KELURAHAN BANJARSENGON KECAMATAN PATRANG KABUPATEN JEMBER - Kiswati, Kiswati; Karnasih, I Gusti Ayu (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Baby massage is useful for increasing the amount and cytotoxicity of the immunity system (natural killer cells), stimulating digestive function as well as discharge, helping to train relaxation, reducing depression and tension, improving alertness, reducing pain, reducing bloating and colic (abdominal pain), increasing breast milk volume, increasing weight, promoting growth, increasing baby concentration and making sleep well, fostering parental and child affection bonds (bonding), as well as improving blood circulation and breathing (Roesli, 2009). Knowledge about baby massage is still unknown to the public, because people still entrust baby massage to baby shamans and the lack of public knowledge to do baby massage. Community service in general to increase community independence through mentoring mother groups and cadres in doing baby massage independently through baby massage education and training by introducing theory and practicing baby massage methods. The results of community service obtained about the level of knowledge of parents about baby massage before education and training are mostly in the sufficient category, a small part of the category is lacking, and after being given education and training, some are in the sufficient category and quite a lot are in the good category. Mothers' skills in massaging before being trained in the category are less 53.8Percent and after being trained the majority of the categories are both 65.4Percent and most mothers are regular in massaging their babies.